2012
DOI: 10.1016/j.jevs.2012.08.190
|View full text |Cite
|
Sign up to set email alerts
|

The soluble form of EIAV receptor encoded by an alternative splicing variant inhibits EIAV infection on target cells

Abstract: Equine lentivirus receptor 1 (ELR1) has been identified as the sole receptor for equine infectious anemia virus (EIAV) and is a member of the tumor necrosis factor receptor (TNFR) superfamily. In addition to the previously described membraneassociated form of ELR1, two other major alternative splicing variant mRNAs were identified in equine monocyte-derived macrophages (eMDMs). One major spliced species (ELR1-IN) contained an insertion of 153 nt, which resulted in a premature stop codon situated 561 nt upstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The genes encoding full‐length ELR1 and gp90 were provided by Jianhua Zhou at the Harbin Veterinary Research Institute, Chinese Academy of Agricultural Sciences (Heilongjiang, China) . The ectodomains of ELR1 (residues 39–206) and gp90 (residues 30–448) were amplified and cloned into the pMT/BiP/TEV‐His expression vector, which was modified from the pMT/BiP/V5‐His plasmid (Invitrogen, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genes encoding full‐length ELR1 and gp90 were provided by Jianhua Zhou at the Harbin Veterinary Research Institute, Chinese Academy of Agricultural Sciences (Heilongjiang, China) . The ectodomains of ELR1 (residues 39–206) and gp90 (residues 30–448) were amplified and cloned into the pMT/BiP/TEV‐His expression vector, which was modified from the pMT/BiP/V5‐His plasmid (Invitrogen, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The genes encoding full-length ELR1 and gp90 were provided by Jianhua Zhou at the Harbin Veterinary Research Institute, Chinese Academy of Agricultural Sciences (Heilongjiang, China). 7,8,35 The ectodomains of ELR1 (residues 39-206) and gp90 (residues 30-448) were amplified and cloned into the pMT/BiP/TEV-His expression vector, which was modified from the pMT/ BiP/V5-His plasmid (Invitrogen, USA). To construct plasmids for the expression of ELR1 containing the mutations Y61A, L70A, G72A and L70AG72A, the pMT-ELR1 expression plasmid was mutated using the QuickChange site-directed mutagenesis kit (Stratagene, USA) according to manufacturer's instructions.…”
Section: Cloningmentioning
confidence: 99%
“…Clinical studies reported that the EIAVFDDV13 attenuated vaccine is approximately 80% effective at inducing immune protection against EIAV. The vaccine confers protection by blocking the ELR1 receptors with an EIAV SU protein, upregulating secretion of an ELR1-transcript variant identified as soluble ELR1 (sELR1) and increasing expression of IFN-β by toll-like receptor 3 (TLR3) (Lin et al, 2013;Ma et al, 2014). Upregulation of secretion of sELR1 is shown to exert antiviral effects and contribute to viral resistance induced by the vaccine (Lin et al, 2013).…”
Section: Equine Infectious Anemia Virusmentioning
confidence: 99%
“…The vaccine confers protection by blocking the ELR1 receptors with an EIAV SU protein, upregulating secretion of an ELR1-transcript variant identified as soluble ELR1 (sELR1) and increasing expression of IFN-β by toll-like receptor 3 (TLR3) (Lin et al, 2013;Ma et al, 2014). Upregulation of secretion of sELR1 is shown to exert antiviral effects and contribute to viral resistance induced by the vaccine (Lin et al, 2013). Unfortunately, soluble viral receptors were constructed and tested for the HIV-1 receptor (CD4) in the mid to late '90s; sCD4+ treatment Phase I and II clinical trials were unable to show effective antiviral properties in vivo (Norkin, 1995).…”
Section: Equine Infectious Anemia Virusmentioning
confidence: 99%